Empowering Veterinary Herd Health Management: Insights into Education, Implementation, and Regulation Across Europe - Marić, Marina; Manghnani, Vidhi; Niemi, Jarkko K; Niine, Tarmo; De Briyne, Nancy; Jansen, Wiebke (MDPI, 2024)
In recent years, integrated veterinary herd health management (VHHM), improving animal health, welfare, food safety, public health, farm management, and economics, has become ever-more important in the European Union due to structural and regulatory advancements. A mixed-methods study analyzed the current state and gaps in VHHM education and training across Europe. Data from 41 European veterinary institutions showed that 83% (n = 34/41) offered VHHM education, either as standalone courses and/or integrated into other subjects. An online survey for veterinarians, primarily working with cattle, poultry, pigs, and small ruminants (75%; n = 86/114), assessed perceived training knowledge gaps and needs. The majority of respondents were unaware of VHHM training programs (69.4%, n = 43/62) or projects (59.6%, n = 59/99) and reported the biggest gaps in VHHM training certification (14%, n = 7/49), followed by soft skills (12%, n = 6/52) and demonstrating VHHM benefits to their clients (9%, n = 5/53). To conclude, while undergraduate VHHM education was generally adequate, enhancing post-graduate certified multi-species training opportunities, incl. soft skills VHHM training were perceived as essential. Our findings also underscored the urgent need for robust economic evaluations of preventive strategies across various animal species to allow veterinarians to better demonstrate VHHM’s direct and indirect benefits to farmers.
Keywords: herd health management; veterinary medicine; animal health management